Auditoria administrativa al sindicato de chóferes profesionales del cantón La Mana y los resultados del periodo 2011 - Reyes Armas, Rodrigo Arturo (2013)
The present investigation project exposes the obtained results after having carried out an administrative audit to the UNION OF PROFESSIONAL CHAUFFEURS OF THE CANTON THE MANNA, during the year 2011; this audit work exposes the procedures applied in the organization and the internal checks that it maintains the entity; also this project the query of the problem of the investigation responds: Which are they the parameters that demand the execution from an Administrative audit to the Union of Professional chauffeurs of the canton The Manna, and the results of the period 2011? The present investigation project is compound for two phases, the first one that corresponds at the introductory part and the second to the chapters that constitute the body of the document in a total of five. This investigation constitutes it a theoretical part and another practical part. It is considered documental for that their objective was reached with the application of theories or advance of general order already existent and whose goods are known in the professional environment of the Accounting. It is considered practice because the necessary information, to achieve the outlined objective, was obtained directly of the reality. To develop the Theoretical Marco of the Investigation it became precise to analyze each one of the variables that are presented as a result of the position of the problem, it was necessary the search of opportune and truthful information in books, scientific articles, pamphlets and pages web that fulfilled the technical requirements characteristic of a scientific writing to my concept. As for the methodology of the investigation, methods like the inductive, deductive and analytic were used, since I consider that they are the most opportune when of executing an audit it is. As for the techniques, it became necessary to appeal to the interview, since it is the most direct method to obtain information on the part of the speaker. The execution of this work, included the evaluation of the internal check by means of an internal check questionnaire, having 65 points as a result on a total of 100 points; inside the discoveries they were had: the absence of a Manual of Functions, and the acting of the collaborators of the Union is not evaluated. As for the confidence level we obtained 65,00%, therefore we have 35,00% of level of control risk; the mensuration of the risks has: risk inherent 35%; risk of control 35,00%; and the detection risk assumed 15%; giving 1,84% of the Risk of Audit as a result. As essential part of this investigation project, they think about summations and recommendations in the Chapter V, these recommendations to my approach will contribute from an appropriate way to the administration of the Union of Professional Chauffeurs of the Canton the Manna.